2023
DOI: 10.3390/jcm12175510
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Back Muscle Dysfunctions in Chronic Low Back Pain: State-of-the-Art and Clinical Implications

Thomas Matheve,
Paul Hodges,
Lieven Danneels

Abstract: Changes in back muscle function and structure are highly prevalent in patients with chronic low back pain (CLBP). Since large heterogeneity in clinical presentation and back muscle dysfunctions exists within this population, the potential role of back muscle dysfunctions in the persistence of low back pain differs between individuals. Consequently, interventions should be tailored to the individual patient and be based on a thorough clinical examination taking into account the multidimensional nature of CLBP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 150 publications
0
9
0
1
Order By: Relevance
“…Many studies have examined contributing factors to LBP, such as genetics, psychological factors, societal status, and physiological factors. However, there is no singular cause of LBP, making it difficult not only to study but also to manage [ 1 , 3 , 4 , 5 , 6 , 7 ]. For physiological factors, lumbar paraspinal musculature has recently been a major focus in LBP research.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have examined contributing factors to LBP, such as genetics, psychological factors, societal status, and physiological factors. However, there is no singular cause of LBP, making it difficult not only to study but also to manage [ 1 , 3 , 4 , 5 , 6 , 7 ]. For physiological factors, lumbar paraspinal musculature has recently been a major focus in LBP research.…”
Section: Introductionmentioning
confidence: 99%
“…For physiological factors, lumbar paraspinal musculature has recently been a major focus in LBP research. Studies have shown the benefit of targeting deep trunk and paraspinal muscles with exercise programs to reduce pain and atrophy [ 7 ]. However, the current understanding of the role of paraspinal musculature in the development, recurrence, and severity of LBP remains limited, especially when it comes to the natural progression (i.e., without intervention) of the paraspinal muscles’ structural changes over time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations